Robust Extracellular pH Modulation by Candida albicans during Growth in Carboxylic Acids - Heather A. Danhof (American Society for Microbiology, 2016)
ABSTRACT The opportunistic fungal pathogen Candida albicans thrives within diverse niches in the mammalian host. Among the adaptations that underlie this fitness is an ability to utilize a wide array of nutrients, especially sources of carbon that are disfavored by many other fungi; this contributes to its ability to survive interactions with the phagocytes that serve as key barriers against disseminated infections. We have reported that C. albicans generates ammonia as a byproduct of amino acid catabolism to neutralize the acidic phagolysosome and promote hyphal morphogenesis in a manner dependent on the Stp2 transcription factor. Here, we report that this species rapidly neutralizes acidic environments when utilizing carboxylic acids like pyruvate, α-ketoglutarate (αKG), or lactate as the primary carbon source. Unlike in cells growing in amino acid-rich medium, this does not result in ammonia release, does not induce hyphal differentiation, and is genetically distinct. While transcript profiling revealed significant similarities in gene expression in cells grown on either carboxylic or amino acids, genetic screens for mutants that fail to neutralize αKG medium identified a nonoverlapping set of genes, including CWT1, encoding a transcription factor responsive to cell wall and nitrosative stresses. Strains lacking CWT1 exhibit retarded αKG-mediated neutralization in vitro, exist in a more acidic phagolysosome, and are more susceptible to macrophage killing, while double cwt1Δ stp2Δ mutants are more impaired than either single mutant. Together, our observations indicate that C. albicans has evolved multiple ways to modulate the pH of host-relevant environments to promote its fitness as a pathogen. IMPORTANCE The fungal pathogen Candida albicans is a ubiquitous and usually benign constituent of the human microbial ecosystem. In individuals with weakened immune systems, this organism can cause potentially life-threatening infections and is one of the most common causes of hospital-acquired infections. Understanding the interactions between C. albicans and immune phagocytic cells, such as macrophages and neutrophils, will define the mechanisms of pathogenesis in this species. One such adaptation is an ability to make use of nonstandard nutrients that we predict are plentiful in certain niches within the host, including within these phagocytic cells. We show here that the metabolism of certain organic acids enables C. albicans to neutralize acidic environments, such as those within macrophages. This phenomenon is distinct in several significant ways from previous reports of similar processes, indicating that C. albicans has evolved multiple mechanisms to combat the harmful acidity of phagocytic cells.